Depletion of Host and Viral Sphingomyelin Impairs Influenza Virus Infection - Audi, Amani; Soudani, Nadia; Dbaibo, Ghassan; Zaraket, Hassan (Frontiers in Microbiology, 2020)
Influenza A virus (IAV) is a major human respiratory pathogen causing annual epidemics as well as periodic pandemics. A complete understanding of the virus pathogenesis and host factors involved in the viral lifecycle is crucial for developing novel therapeutic approaches. Sphingomyelin (SM) is the most abundant membrane sphingolipid. It preferentially associates with cholesterol to form distinct domains named lipid rafts. Sphingomyelinases, including acid sphingomyelinase (ASMase), catalyzes the hydrolysis of membrane SM and consequently transform lipid rafts into ceramide-enriched membrane platforms. In this study, we investigated the effect of SM hydrolysis on IAV propagation. Depleting plasma membrane SM by exogenous bacterial SMase (bSMase) impaired virus infection and reduced virus entry, whereas exogenous SM enhanced infection. Moreover, the depletion of virus envelope SM also reduced virus infectivity and impaired its attachment and internalization. Nonetheless, inhibition of ASMase by desipramine did not affect IAV infection. Similarly, virus replication was not impaired in Niemann-Pick disease type A (NPA) cells, which lack functional ASMase. IAV infection in A549 cells was associated with suppression of ASMase activity starting at six hours post-infection. Our data reveals that intact cellular and viral envelope SM is required for efficient IAV infection. Therefore, SM metabolism can be a potential target for therapeutic intervention against influenza virus infection.